The Portsmouth protocol for intra‐operative ultrasound of the small bowel in Crohn's disease. (17th November 2019) - Celentano, V.; Beable, R.; Ball, C.; Flashman, K.G.; Reeve, R.; Holmes, A.; Fogg, C.; Harper, M.; Higginson, A.
Abstract: Aim: Bowel preservation is paramount in Crohn's disease surgery as affected patients are typically young adults at risk of having several abdominal surgical procedures during their lifetime. Intra‐operative assessment of the extent and location of Crohn's disease is not standardized and is left to a mixture of the surgeon's experience, tactile feedback, macroscopic appearance and preoperative imaging. The aim of this study was to describe the technical steps of a standardized protocol for intra‐operative ultrasound assessment of the small bowel in patients undergoing surgery for ileocolic Crohn's disease. Method: After laparoscopic mobilization of the bowel, a periumbilical incision is performed for extracorporeal division of the mesentery and the resection and anastomosis. A gastrointestinal consultant radiologist, with expertise in Crohn's disease imaging and abdominal ultrasound, performs full intra‐operative assessment of the small bowel by applying a sterile ultrasound probe directly to the bowel, prior to resection being performed by the surgeon. The bowel is assessed through the wound protector with a sterile technique and the length, location and number of segments is documented together with further quantitative assessment using the METRIC (MR enterography or ultrasound in Crohn's disease) scoring guide. Results: A step‐by‐step protocol for intra‐operative ultrasound evaluation of the entire small bowel is described. Conclusions: A standardized approach to intra‐operative evaluation of the extent and location of Crohn's disease is desirable. Intra‐operative ultrasound may provide added value for assessment of proximal and multifocal Crohn's disease.